Students' Perceptions of Using Youglish for Vocabulary Enrichment in a Speaking Class - Gunawan, Bella Trivena; Musyarofah, Lailatul; Sabat, Yuliyanto (Journey: Journal of English Language and Pedagogy, 2026)
This study investigates students’ perceptions and learning experiences using YouGlish as a vocabulary enrichment tool in a speaking class at PGRI Delta University. Adopting a qualitative descriptive design, data were gathered through questionnaires, semi-structured interviews, and classroom observations involving 10 third-semester English Education students. The findings reveal that students held overwhelmingly positive perceptions, with 100% of participants agreeing on the platform's utility and ease of use. Students specifically valued authentic video examples, diverse accents, and synchronized transcripts as primary learning supports. Results indicate that YouGlish successfully facilitated both intentional and incidental vocabulary gains, with students acquiring 5 to 20 new words per session while improving pronunciation awareness and speaking confidence. Although minor technical challenges like advertisements were identified, they did not diminish the tool’s pedagogical effectiveness. The study concludes that YouGlish is an effective supplementary digital tool that fosters learner autonomy and provides meaningful, authentic language exposure in EFL contexts. These results suggest that integrating multimodal digital resources can significantly enhance lexical development in speaking activities.